Analisis Karakteristik Pelanggan, Reputasi Perusahaan, dan CRM Terhadap Kreasi Nilai Pelanggan (Survei pada Bank Digital di Jawa Barat) - Supriyadi, Tatang; Muhammad Iffan; Arjuna Rizaldi; Andina Dwijayanti; Panji Pramuditha (JEMBA, 2025)
The purpose of this research is to examine: (1) the description of customer characteristics, corporate reputation, and Customer Relationship Management (CRM) in relation to customer value creation among digital bank clients in West Java; (2) the magnitude of the effects of these variables on customer value creation; (3) the direct impact of customer characteristics on customer value creation; (4) the direct impact of corporate reputation on customer value creation; and (5) the direct impact of CRM on customer value creation. A quantitative research design was applied using an explanatory survey method to identify and test causal relationships between the study variables. The variables under investigation consist of customer characteristics, corporate reputation, CRM, and customer value creation, based on a sample of 123 respondents from digital banking users. The empirical results reveal that customer characteristics significantly affect customer value creation with an influence of 22.69%. Corporate reputation demonstrates the highest total contribution of 42.06% to customer value creation, while CRM shows a 12.28% effect. Overall, the findings highlight that corporate reputation is the most influential factor in strengthening customer value creation in digital banking, complemented by effective relationship management and supportive customer attributes